A preparation method of oxide-selenide heterostructure material and its application in lithium-sulfur battery

By using the oxide-selenide heterojunction prepared by the hydrothermal method in lithium sulfur batteries as the positive electrode material additive, the problems of poor electron transfer and polysulfide shuttle effect during charging and discharge of lithium sulfur batteries are solved, and higher specific capacity and rate performance are achieved.

CN116264277BActive Publication Date: 2025-03-18QINGDAO UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111526823.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-14
Publication Date
2025-03-18
Estimated Expiration
2041-12-14

AI Technical Summary

Technical Problem

During the charging and discharging process, the electrical insulation of sulfur and lithium sulfide affects electron transfer, resulting in insufficient material utilization, and the shuttle effect of polysulfide reduces capacity and cycling performance.

Method used

The polyaniline-metal oxide composite material was prepared by hydrothermal method, and in situ selenization was made by chemical vapor phase method to form an oxide-selenide heterojunction as an additive for the positive electrode material of lithium sulfur batteries.

Benefits of technology

Through the dual-function strategy of adsorption-catalytic, the shuttle effect of polysulfide is suppressed, the specific capacity and rate performance of lithium-sulfur batteries are improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116264277B_ABST
    Figure CN116264277B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemical energy storage materials, and specifically relates to a method for preparing an oxide-selenide heterostructure material and its application in a lithium-sulfur battery. A metal oxide is intercalated and polymerized with aniline by a hydrothermal method to form a nano-flower sheet-like structure polyaniline-metal oxide composite material with a high specific surface area, and then the metal oxide is in-situ selenized by a chemical vapor phase method through a pre-selenium source to form an oxide-selenide heterojunction. The nitrogen-selenium doped carbon@oxide-selenide heterojunction prepared by the present invention retains the morphology of the precursor polyaniline-metal oxide, and due to the presence of the heterojunction, the adsorption-catalysis dual function effect can be achieved in suppressing the lithium polysulfide shuttle effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical energy storage materials, and in particular relates to a method for preparing an oxide-selenide heterostructure material and an application thereof in a lithium-sulfur battery. Background Art

[0002] With the introduction of safe, low-cost, and environmentally friendly electrochemical energy storage devices, lithium-ion batteries, as the best commercial secondary battery system, are increasingly used in electric vehicles and portable electronic devices. As one of the lithium-ion battery systems, lithium-sulfur batteries have excellent theoretical specific capacity (1672 mAh g -1 ), theoretical energy density (2600Wh Kg -1 ) and sulfur positive electrode have been widely studied due to their high crustal abundance and environmental friendliness. It has gradually entered the field of vision of researchers and has been widely studied. However, the development and practical application of lithium-sulfur batteries have encountered major challenges: First, due to the inherent electrical insulation of sulfur and lithium sulfide, it will affect electron transfer, thus preventing the active materials from being fully utilized. Secondly, during the charge and discharge process, there is a huge density difference between the reactants and products, which will cause severe shrinkage and expansion of the electrode, reducing the cycle durability and service life of the battery. Finally, the shuttle effect of polysulfides will consume active materials, resulting in a rapid decrease in capacity and poor coulombic efficiency.

[0003] In order to solve these problems, people have conducted a lot of research on sulfur cathodes. In order to improve conductivity and cope with the volume expansion of sulfur during charging and discharging, some porous, tubular, core-shell inactive substances (such as carbon) are added to the sulfur cathode as supporting skeletons and electron channels. At the same time, the exploration and mechanism research of various sulfur host materials to inhibit the polysulfide shuttle effect has never stopped. According to the different forces, these strategies can be roughly divided into two categories: physical constraints and chemical adsorption. Physical constraint strategies usually spatially restrict the materials with structural characteristics of polysulfide hosts. Generally speaking, regional structures and large specific surface areas and lower densities, such as porous structures, core-shell structures and layered structures, are more attractive. However, the weak affinity and adsorption of carbon-based materials for lithium polysulfides determine that pure carbon materials are not enough as an ideal sulfur-fixing material. Therefore, in dealing with the lithium polysulfide shuttle effect, a dual strategy combining physical constraints and chemical effects is often required.

[0004] In the strategy of inhibiting the shuttling effect of polysulfides, the role of catalysts has received more and more attention. The effects of catalysts on polysulfides generally include adsorption and catalysis. Among them, transition metal oxides have become a more suitable choice due to their adsorption effect on polysulfides. At the same time, the role of selenides in promoting the conversion kinetics of polysulfides has also been confirmed in many studies. However, although Yang et al. prepared the heterostructure of WS2-WO3, it can be applied to the positive electrode material of lithium-sulfur batteries (Adv. Energy Mater. 2020, 2000091); Kang et al. reported the heterostructure of TiO2-TiN, and the results showed that the heterojunction can improve the capacity and cycle performance of lithium-sulfur batteries (Energy Environ. Sci., 2019, 12, 3144--3155). However, no researchers have reported the combination of oxides and selenides into heterostructures and applied them to lithium-sulfur batteries. Summary of the invention

[0005] The present invention aims at a method for preparing an oxide-selenide heterostructure material and its application in a lithium-sulfur battery.

[0006] To achieve the above purpose, the present invention adopts the following technical solution:

[0007] A method for preparing an oxide-selenide heterostructure material comprises the following steps: intercalating and polymerizing a metal oxide with aniline by a hydrothermal method to form a nano-flower-like polyaniline-metal oxide composite material with a high specific surface area; and then in-situ selenizing the metal oxide by a chemical vapor method by pre-positioning a selenium source to form an oxide-selenide heterojunction.

[0008] Specifically:

[0009] (1) Preparation of polyaniline-metal oxide precursor: Aniline is dispersed in deionized water, and metal oxide is added; after adjusting the pH of the system to 2-5 with acid, the system is transferred to a hydrothermal reactor for heat treatment at 120-180° C. for 12-36 h after ultrasonic treatment, and then washed and dried to obtain polyaniline-metal oxide precursor powder;

[0010] (2) Preparation of nitrogen-selenium doped carbon@oxide-selenide heterojunction: The polyaniline-metal oxide precursor is mixed with selenium powder, heated to 450-650°C at a heating rate of 3-10°C / min in an Ar / H2 atmosphere, and then slowly cooled to room temperature to obtain a powder nitrogen-selenium doped carbon@oxide-selenide heterojunction.

[0011] The metal oxide is iron, vanadium, niobium or nickel oxide.

[0012] The metal oxide is ferroferric oxide (Fe3O4), vanadium pentoxide (V2O5), niobium pentoxide (Nb2O5) or nickel oxide (NiO).

[0013] In the step 2), the polyaniline-metal oxide precursor is placed in a porcelain boat, the porcelain boat is placed in the middle high temperature zone of the tube furnace, and then the porcelain boat carrying the selenium powder is placed upstream of the air flow of the tube furnace, and fired in an Ar / H2 atmosphere to obtain a nitrogen-selenium doped carbon@oxide-selenide heterojunction; the mass ratio of the selenium powder to the precursor is 1 to 10.

[0014] Furthermore, the porcelain boat carrying the polyaniline-metal oxide precursor is placed in the middle high temperature zone of the tube furnace, while the porcelain boat carrying the selenium powder is placed upstream of the air flow of the tube furnace. This adjustment comprehensively considers the temperature difference between the sublimation temperature of the selenium powder and the selenization temperature of the polyaniline-metal oxide precursor, thereby achieving the purpose of fully utilizing the selenium powder.

[0015] The obtained oxide-selenide heterostructure material is a stable oxide-selenide heterostructure material with nano-flower cluster morphology prepared according to the method.

[0016] The oxide-selenide heterostructure material is used as a positive electrode material additive for lithium-sulfur batteries.

[0017] A lithium-sulfur battery positive electrode material, wherein the oxide-selenide heterostructure material is added to the positive electrode material, wherein the added amount of the material is 10%-20%.

[0018] The heterojunction material is mixed with the conductive material and sulfur in a mass ratio of (0.5-1.5):(4.5-5.5):(1-3), the mixture is ground and evenly mixed, and after mixing, heat-treated in a hydrothermal autoclave at 155-165° C. for 10-24 h to obtain a lithium-sulfur battery positive electrode material.

[0019] The conductive material is conductive carbon black, carbon nanotube conductive agent, Ketjen black or super-P carbon black.

[0020] The ground and mixed carbon disulfide is used as a solvent to uniformly disperse the mixture through ultrasonication, the uniform dispersion is dried, and the dried dispersion is heat-treated in a hydrothermal kettle.

[0021] The sulfur positive electrode was prepared using the lithium-sulfur battery positive electrode material obtained above: the lithium-sulfur battery positive electrode material was mixed with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1, N-methylpyrrolidone was used as a solvent, the mixture was scraped onto an aluminum foil, and dried at 60°C in a vacuum drying oven for 12 hours to obtain a sulfur positive electrode.

[0022] The advantages of the present invention are:

[0023] The present invention combines a polyaniline-metal oxide composite material with a selenide to obtain a nitrogen-selenium doped carbon@oxide-selenide heterojunction composite material, which is used as a positive electrode material additive for a lithium-sulfur battery. The additive obtained by the present invention inhibits the shuttle effect of polysulfides through an adsorption-catalysis dual-functional strategy; specifically:

[0024] 1. The additive of the present invention uses polyaniline-metal oxide, which is a precursor with excellent structure and components. First, the structure of its nano-flower sheet has a high specific surface area, which can provide a broad platform for polysulfide conversion reaction when used as a catalyst material. Secondly, polyaniline is a polymer containing amino groups, and nitrogen-doped carbon can be obtained after high-temperature calcination. Nitrogen doping can greatly improve the conductivity of carbon. At the same time, due to the presence of polyaniline intercalated metal oxide, a structure in which the oxide layer and the carbon layer are closely adjacent can be obtained after calcination, so that the electronic conductivity of the material and the affinity of polysulfide are both achieved.

[0025] 2. The chemical vapor phase selenization method used in the present invention has excellent and controllable selenization effect and has little effect on the morphology of the precursor, retaining the nano-flower sheet morphology of the precursor, and also obtaining an oxide-selenide heterojunction in the same sheet layer.

[0026] 3. In the process of preparing nitrogen-selenium doped carbon@oxide-selenide heterojunction, the present invention uses vanadium trioxide as a raw material. Vanadium trioxide, as a polar material, can modify non-polar carbon materials and increase their adsorption effect on polysulfides; and the presence of selenium defects is used to provide more electrophilic active sites on the surface of the material layer, which has excellent affinity and catalytic effect on lithium polysulfide rich in lone pair electrons; due to the presence of polyaniline intercalated metal oxide, the additive obtained by the present invention can obtain a structure in which the oxide layer and the carbon layer are closely adjacent after calcination, and with the co-doping of nitrogen and selenium, the electronic conductivity of the material and the affinity of polysulfide are both obtained, thereby greatly improving the conductivity of the carbon layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Scanning electron microscope image of the polyaniline-vanadium pentoxide precursor provided in an embodiment of the present invention (reaction condition PH=3).

[0028] Figure 2 This is a scanning electron microscope image of nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide provided in an embodiment of the present invention.

[0029] Figure 3 This is an X-ray diffraction pattern of nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide provided in an embodiment of the present invention.

[0030] Figure 4 This is a scanning electron microscope image of the nitrogen-doped carbon@vanadium oxide provided by the present invention.

[0031] Figure 5 This is the X-ray diffraction pattern of nitrogen-doped carbon@vanadium oxide provided by the present invention.

[0032] Figure 6 This is a scanning electron microscope image of the polyaniline-vanadium pentoxide precursor provided by the present invention (reaction condition PH=2.5).

[0033] Figure 7 A comparison diagram of the charge and discharge curves of nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide (A), nitrogen-doped carbon@vanadium oxide (B) and granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide (C) provided by the present invention.

[0034] Figure 8 This is a rate comparison diagram of nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide (A), nitrogen-doped carbon@vanadium oxide (B) and granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide (C) provided by the present invention. DETAILED DESCRIPTION

[0035] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0036] The present invention obtains nitrogen-selenium doped carbon@oxide-selenide heterojunction (NC@MO-MSe) in situ, wherein a polyaniline-metal oxide composite material obtained by controlling the reaction conditions of polyaniline intercalated metal oxide is used as a precursor, and vapor phase selenization is performed by pre-adding an appropriate amount of selenium powder to obtain a nitrogen-selenium doped carbon@oxide-selenide heterojunction in the form of a nanoflower ball assembled by nanosheets, which is used as a positive electrode additive for lithium-sulfur batteries, achieving an "adsorption-catalysis" dual-functional strategy of promoting polysulfide conversion and inhibiting polysulfide shuttling effect.

[0037] Embodiment 1:

[0038] (1) Preparation of polyaniline-ferroferric oxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.36 g of Fe3O4 powder was added and stirring was continued; the suspension was titrated to pH = 3 with the prepared HCl, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 120°C for 28 h, washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-ferroferric oxide precursor powder.

[0039] (2) Obtaining nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction: The polyaniline-iron tetroxide precursor is placed in a porcelain boat, and selenium powder is placed in front. In an Ar / H2 atmosphere, the temperature is raised to 550°C at 5°C / min and maintained for 3 h, and then slowly cooled to room temperature to obtain a powdered nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction; wherein the mass ratio of the polyaniline-iron tetroxide precursor to the selenium powder is 1:4.

[0040] The porcelain boat carrying the polyaniline-metal oxide precursor is placed in the middle high temperature zone of the tube furnace, while the porcelain boat carrying the selenium powder is placed at the upstream of the air flow of the tube furnace. This adjustment comprehensively considers the temperature difference between the sublimation temperature of the selenium powder and the selenization temperature of the polyaniline-metal oxide precursor, thereby achieving the purpose of fully utilizing the selenium powder.

[0041] The nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction is obtained by using the above embodiment as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0042] 1) Obtaining sulfur / nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction: The nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction obtained above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0043] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@iron oxide-iron selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and N-methylpyrrolidone was used as solvent. The mixture was scraped onto aluminum foil and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0044] Embodiment 2:

[0045] (1) Preparation of polyaniline-vanadium pentoxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.36 g of V2O5 powder was added and stirring was continued; the suspension was titrated with prepared HCl to pH = 3, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 120°C for 28 h, washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-vanadium pentoxide precursor powder.

[0046] (2) Obtaining nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: A polyaniline-vanadium pentoxide precursor is placed in a porcelain boat, and the pre-placed selenium powder is heated to 550°C at 5°C / min under an Ar / H2 atmosphere and maintained for 3 h, and then slowly cooled to room temperature to obtain a powdered nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction, wherein the mass ratio of the polyaniline-ferroferric oxide precursor to the selenium powder is 1:4.

[0047] The above embodiment is used to obtain nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0048] 1) Obtaining sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: The nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction obtained above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0049] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, N-methylpyrrolidone was used as solvent, the mixture was scraped onto aluminum foil, and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0050] Embodiment 3:

[0051] (1) Preparation of polyaniline-niobium pentoxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.36 g of Nb2O5 powder was added and stirring was continued; the suspension was titrated with the prepared HCl to pH = 3, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 120°C for 28 h (12-36), washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-niobium pentoxide precursor powder.

[0052] (2) Obtaining nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction: Place the polyaniline-niobium pentoxide precursor in a porcelain boat, add a certain mass ratio (1:4) of selenium powder in an Ar / H2 atmosphere, heat to 550°C (450-650°C) at 5°C / min, maintain for 3h (1-5h), and then slowly cool to room temperature to obtain powder nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction.

[0053] The nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction is obtained by using the above embodiment as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0054] 1) Obtaining sulfur / nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction: The nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction obtained above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0055] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@niobium oxide-niobium selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and N-methylpyrrolidone was used as solvent. The mixture was scraped onto aluminum foil and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0056] Embodiment 4:

[0057] (1) Preparation of polyaniline-nickel oxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.36 g of NiO powder was added and stirring was continued; the suspension was titrated with the prepared HCl to pH = 3, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 120°C for 28 h (12-36), washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-nickel oxide precursor powder.

[0058] (2) Preparation of nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction: Place the polyaniline-nickel oxide precursor in a porcelain boat, add a certain mass ratio (1:4) of selenium powder in an Ar / H2 atmosphere, heat the mixture to 550°C (450-650°C) at a rate of 5°C / min, and maintain for 3h (1-5h). Then slowly cool the mixture to room temperature to obtain a powdered nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction.

[0059] The nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction is obtained by using the above embodiment as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0060] 1) Obtaining sulfur / nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction: The nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction prepared above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0061] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@nickel oxide-nickel selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and N-methylpyrrolidone was used as solvent. The mixture was scraped onto aluminum foil and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0062] Embodiment 5:

[0063] (1) Preparation of polyaniline-vanadium pentoxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.24 g of V2O5 powder was added and the stirring was continued. The suspension was titrated with the prepared HCl to pH = 3, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 140°C for 28 h, washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-vanadium pentoxide precursor powder.

[0064] (2) Preparation of nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: A polyaniline-vanadium pentoxide precursor was placed in a porcelain boat, and a certain mass ratio (1:4) of selenium powder was placed in front of it. The temperature was raised to 550°C at 5°C / min in an Ar / H2 atmosphere and maintained for 2 h. Then the temperature was slowly cooled to room temperature to obtain a powdered nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction.

[0065] The above embodiment is used to obtain nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0066] 1) Obtaining sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: The nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction prepared above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0067] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, N-methylpyrrolidone was used as solvent, the mixture was scraped onto aluminum foil, and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0068] Embodiment 6:

[0069] (1) Preparation of polyaniline-vanadium pentoxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.48 g of V2O5 powder was added and stirring was continued; the suspension was titrated with prepared HCl to pH = 3, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 160°C for 28 h, washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-vanadium pentoxide precursor powder.

[0070] (2) Obtaining nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: Place a polyaniline-vanadium pentoxide precursor in a porcelain boat, pre-place a certain mass ratio (1:4) of selenium powder, and heat it to 550°C (450-650°C) at 5°C / min in an Ar / H2 atmosphere, maintain it for 3h (1-5h), and then slowly cool it to room temperature to obtain a powdered nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction.

[0071] The above embodiment is used to obtain nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0072] 1) Obtaining sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: The nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction obtained above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0073] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and N-methylpyrrolidone was used as solvent. The mixture was scraped onto aluminum foil and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0074] The morphology and component analysis of the heterojunctions obtained in the above embodiments are as follows:

[0075] Specifically, the morphology was characterized by a scanning electron microscope, the model of which was a JEOL Ltd., JSM-6700F, with an electron excitation voltage of 8 kV and a current of 10 μA. The component analysis was characterized by an X-ray diffraction, the model was a Japanese Rigaku D-max-YA, 40 kV, and the copper target excitation ray Cu Kɑ was used as the light source.

[0076] Taking the nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction obtained in Example 2 as an example, the above morphology characterization and component analysis refer to Figure 1 and Figure 2 The obtained polyaniline-vanadium pentoxide precursor powder exhibits a nanoflower-like morphology composed of nanosheets ( Figure 1 ), there is no stacking and agglomeration between the nanosheets, and they are evenly dispersed. After vapor phase selenization, the obtained nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterostructure material exhibits a nanoflower-like morphology assembled from nanosheets ( Figure 2 ), and its morphology is consistent with that of its precursor, indicating that after the high-temperature vapor phase selenization process, the nanoflower-like morphology is stable and not damaged. The component analysis results show that the obtained nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterostructure mainly consists of a two-phase composite material ( Figure 3 ), wherein the two phases are V2O3 and V1.156Se2. It can be seen that the heterojunction obtained in Example 2 has a nanoflower-like structure, is evenly dispersed and has good stability, and its components include two crystalline phases of V2O3 and V1.156Se2.

[0077] Comparative Example 1

[0078] (1) Preparation of polyaniline-vanadium pentoxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.36 g of V2O5 powder was added and stirring was continued; the suspension was titrated to pH = 3 with the prepared HCl, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 120°C for 28 h (12-36), washed with deionized water and ethanol, and dried at 60°C to obtain a polyaniline-vanadium pentoxide precursor powder.

[0079] (2) Preparation of nitrogen-selenium doped carbon@vanadium oxide: The polyaniline-vanadium pentoxide precursor was placed in a porcelain boat, heated to 550°C (450-650°C) at 5°C / min in an Ar / H2 atmosphere and maintained for 3 h, and then slowly cooled to room temperature to obtain powdered nitrogen-selenium doped carbon@vanadium oxide (see Figure 4 ).

[0080] Depend on Figure 4 It can be seen that the nitrogen-selenium doped carbon@vanadium oxide in the comparative example exhibits a nanoflower-like morphology composed of nanosheets, and the nanoflowers are evenly dispersed. The component analysis results show that the main crystalline phase structure of the nitrogen-selenium doped carbon@vanadium oxide is V2O3( Figure 5 ), which can be used as a comparative sample for Example 2.

[0081] The above embodiment is used to obtain nitrogen-selenium doped carbon@vanadium oxide as a positive electrode material additive for lithium-sulfur batteries, specifically:

[0082] 1) Obtaining sulfur / nitrogen-selenium doped carbon@vanadium oxide: The nitrogen-selenium doped carbon@vanadium oxide prepared above is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermaled at 155°C for 10 h to obtain sulfur / nitrogen-selenium doped carbon@vanadium oxide for subsequent preparation of sulfur positive electrode.

[0083] 2) Preparation of sulfur positive electrode: sulfur / nitrogen-selenium doped carbon@vanadium oxide was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, and N-methylpyrrolidone was used as solvent. The mixture was scraped onto aluminum foil and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0084] Comparative Example 2

[0085] (1) Preparation of polyaniline-vanadium pentoxide precursor: 0.12 g of aniline was dispersed in 80 ml of deionized water, and after magnetic stirring, 0.36 g of V2O5 powder was added and stirring was continued; the suspension was titrated with prepared HCl to pH = 2.5, and after ultrasonication, it was transferred to a hydrothermal autoclave and heat treated at 120°C for 28 h (12-36), washed with deionized water and ethanol, and dried at 60°C to obtain a granular polyaniline-vanadium pentoxide precursor.

[0086] (2) Preparation of granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: A polyaniline-vanadium pentoxide precursor is placed in a porcelain boat, and a certain mass ratio (1:4) of selenium powder is placed in front of it. In an Ar / H2 atmosphere, the temperature is raised to 550°C (450-650°C) at 5°C / min and maintained for 3h (1-5h), and then slowly cooled to room temperature to obtain a powdered nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction.

[0087] Depend on Figure 4 It can be seen that the polyaniline-vanadium pentoxide precursor in the comparative example obtained by changing the reaction pH value no longer exhibits a nanoflower morphology assembled from nanosheets, and its morphology is characterized by particles formed by agglomeration of nanosheets, and the particles are unevenly dispersed and have agglomeration characteristics.

[0088] The above embodiment is used to obtain a granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction as a positive electrode material additive for a lithium-sulfur battery, specifically:

[0089] 1) Preparation of sulfur / granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction: The prepared granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction is mixed with conductive carbon black and sulfur in a ratio of 1:5:2 (mass ratio), and hydrothermally heated at 155°C for 10 h to obtain a sulfur / granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction for subsequent preparation of a sulfur positive electrode.

[0090] 2) Preparation of sulfur positive electrode: sulfur / granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterojunction was mixed with conductive carbon black and polyvinylidene fluoride in a ratio of 8:1:1, N-methylpyrrolidone was used as solvent, the mixture was scraped onto aluminum foil, and dried in a vacuum drying oven at 60°C for 12 h to obtain a sulfur positive electrode.

[0091] The positive electrode materials were obtained by using the above-mentioned Example 2, Comparative Example 1 and Comparative Example 2, and button batteries were assembled to evaluate their electrochemical performance:

[0092] The button battery is assembled as follows: in a glove box filled with high-purity argon (purity of 99.999%), prepare the positive electrode sheet, diaphragm, battery shell, metal lithium negative electrode, electrolyte and other battery assembly materials, and maintain the oxygen and water concentration in the glove box below 0.1ppm; assemble the battery in the order of negative electrode shell, metal lithium sheet, diaphragm, positive electrode sheet, metal gasket, metal shrapnel and positive electrode shell. During the assembly process, use a pipette to drip lithium-sulfur battery electrolyte on the surface of the metal lithium sheet and the diaphragm, respectively. The amount of electrolyte is 15μL, and the electrolyte composition is 1mol. L-1LiTFSI (lithium bistrifluoromethylsulfonamide) is dissolved in DOL (1,3-pentane oxide) / DME (1,2-dimethoxyethane) (the volume ratio of DOL and DME is 1:1), and the electrolyte contains 1% (mass fraction) of lithium nitrate (LiNO3) additive; a hydraulic button battery packaging machine is used to package the above-assembled battery, and the pressure is controlled at 6-7MPa.

[0093] 1) Charge and discharge curve of lithium-sulfur battery positive electrode:

[0094] Specifically, the above lithium-sulfur battery was charged and discharged using a Landian electrochemical test system (LAND CT2001A), with a test voltage range of 1.7 to 2.8 V (vs. Li+ / Li) and a test current density of 0.2 C (1 C = 1675 mA g-1). All tests were performed by discharging first and then charging (see Figure 7 ).

[0095] Depend on Figure 7 A It can be seen that when nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterostructure is used as an additive for lithium-sulfur batteries, the battery has a higher charge and discharge specific capacity at a current density of 0.2C, and its discharge specific capacity is as high as 1250mAh / g. In contrast, nitrogen-doped carbon@vanadium oxide ( Figure 7 B) and granular nitrogen-selenium-doped carbon@vanadium oxide-vanadium selenide ( Figure 7C) have relatively low discharge specific capacities, which are 1110 mAh / g and 1090 mAh / g respectively. The higher discharge specific capacity is due to the following advantages of the nitrogen-selenium doped carbon@oxide-selenide heterojunction as a lithium-sulfur additive in the present invention: vanadium trioxide, as a polar material, can modify non-polar carbon materials and increase their adsorption of polysulfides; the presence of selenium defects provides more electrophilic active sites on the surface of the material layer, which has excellent affinity and catalytic effects on lithium polysulfides rich in lone pair electrons; the additive obtained by the present invention can obtain a structure in which the oxide layer and the carbon layer are closely adjacent after calcination due to the presence of polyaniline intercalated metal oxide, and the co-doping of nitrogen and selenium makes the electronic conductivity of the material and the affinity of polysulfides have both, thereby greatly improving the conductivity of the carbon layer; at the same time, the nanoflower morphology obtained by the present invention can greatly increase the specific surface area of ​​the additive sample and increase the active sites of the adsorption-catalysis dual function. In contrast, the granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide has less exposed surface and less reactive sites, so its adsorption-catalysis is weaker, the utilization rate of active sulfur material is lower, and therefore the battery capacity is lower.

[0096] 2) Rate performance of lithium-sulfur battery positive electrode:

[0097] Specifically, the current densities selected for rate performance are 0.2C, 0.5C, 0.8C, 1C, 1.5C and 2C, and the voltage range is 1.7 to 2.8V (vs. Li+ / Li). All tests are performed by discharging first and then charging (see Figure 8 ).

[0098] Depend on Figure 8 It can be seen that when nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterostructure is used as an additive for lithium-sulfur batteries, the battery has a higher charge and discharge specific capacity at different current densities (such as 0.2C, 0.5C, 0.8C, 1C, 1.5C and 2C). Taking high rate 2C as an example, when nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide heterostructure is used as an additive for lithium-sulfur batteries, the battery's discharge specific capacity is as high as 690mAh / g. In comparison, nitrogen-doped carbon@vanadium oxide ( Figure 8 B) and granular nitrogen-selenium-doped carbon@vanadium oxide-vanadium selenide ( Figure 8C) When used as a lithium-sulfur battery additive, its discharge specific capacity is 602mAh / g and 610mAh / g respectively. In the present invention, when the nitrogen-selenium doped carbon@oxide-selenide heterojunction is used as a lithium-sulfur additive, the lithium-sulfur battery shows better rate performance, and the reasons are as follows: vanadium trioxide, as a polar material, can modify non-polar carbon materials and increase their adsorption effect on polysulfides; the presence of selenium defects is used to provide more electrophilic active sites on the surface of the material layer, which has excellent affinity and catalytic effects on lithium polysulfides rich in lone pair electrons; the additive obtained by the present invention can obtain a structure in which the oxide layer and the carbon layer are closely adjacent after calcination due to the presence of polyaniline intercalated metal oxide, and the co-doping of nitrogen and selenium makes the electronic conductivity of the material and the affinity of polysulfides have both, and thus the conductivity of the carbon layer is greatly improved; at the same time, the nanoflower morphology obtained by the present invention can greatly increase the specific surface area of ​​the additive sample and increase the active sites of the adsorption-catalysis dual function. In contrast, the granular nitrogen-selenium doped carbon@vanadium oxide-vanadium selenide has less exposed surface and less reactive sites, so its adsorption-catalysis effect is weaker and the battery rate performance is poor.

Claims

1. A method for preparing an oxide-selenide heterostructure material, characterized in that: Aniline is used to intercalate and polymerize metal oxides by a hydrothermal method to form a nano-flower-like polyaniline-metal oxide composite material with a high specific surface area, and then a selenium source is pre-placed and the metal oxide is selenized in situ by a chemical vapor method to form an oxide-selenide heterostructure material; Specifically: Step (1) Preparation of polyaniline-metal oxide precursor: Aniline is dispersed in deionized water, and metal oxide is added; after adjusting the pH of the system to 3-5 with acid, the mixture is transferred into a hydrothermal reactor for heat treatment at 120-180° C. for 12-36 hours after ultrasonic treatment, and then washed and dried to obtain polyaniline-metal oxide precursor powder; Step (2) obtaining nitrogen-selenium doped carbon@oxide-selenide heterojunction: mixing a polyaniline-metal oxide precursor with selenium powder, heating the mixture to 450-650°C at a heating rate of 3-10°C / min in an Ar / H2 atmosphere, calcining the mixture for 2-6 h, and then slowly cooling the mixture to room temperature to obtain a powdered nitrogen-selenium doped carbon@oxide-selenide heterostructure material; The mass ratio of selenium powder to polyaniline-metal oxide precursor is 1 to 10; The metal oxide is vanadium pentoxide (V2O5).

2. The method for preparing the oxide-selenide heterostructure material according to claim 1, characterized in that: The step (2) is to place the polyaniline-metal oxide precursor in a porcelain boat, the porcelain boat is placed in the middle high temperature zone of the tube furnace, and then the porcelain boat carrying the selenium powder is placed upstream of the air flow of the tube furnace, and calcined in an Ar / H2 atmosphere to obtain a nitrogen-selenium doped carbon@oxide-selenide heterostructure material.

3. An oxide-selenide heterostructure material, characterized in that: A stable oxide-selenide heterostructure material with nano-flower cluster morphology prepared by the method of claim 1.

4. An application of the material according to claim 3, characterized in that: The oxide-selenide heterostructure material is used as a positive electrode material additive for lithium-sulfur batteries.

5. A positive electrode material for a lithium-sulfur battery, characterized in that: The oxide-selenide heterostructure material according to claim 4 is added to the positive electrode material, wherein the added amount of the material is 10%-20%.

6. The positive electrode material for a lithium-sulfur battery according to claim 5, characterized in that: The heterogeneous structure material is mixed with the conductive material and sulfur in a mass ratio of (0.5-1.5): (4.5-5.5): (1-3), the mixture is ground and evenly mixed, and after mixing, heat-treated in a hydrothermal autoclave at 155-165° C. for 10-24 h to obtain a lithium-sulfur battery positive electrode material.

Citation Information

Patent Citations

  • Preparation method for metal oxide@metal composite / graphene core-shell semiconductor material with heterojunction interface effect

    CN108321378A

  • Preparation method and application of Ni3Se4 / NiO heterojunction composite material

    CN110093626A

  • Selenium metal compound-carbon material-sulfur composite positive electrode material, preparation method and application

    CN113410463A